2021
DOI: 10.1002/asi.24447
|View full text |Cite
|
Sign up to set email alerts
|

Meaning‐making on gender: Deeply meaningful information in a significant life change among transgender people

Abstract: The purpose of this paper is to report on the seeking of deeply meaningful information, also including embodied information, connected to significant, intensely personal life changes having lifelong impacts. The concepts of "meaning-making," "transitioning," and information seeking in "deeply meaningful and profoundly personal contexts" are used in order to understand transgender individuals' information seeking in the contexts of gender identity formation. Based on the literature, emotions and information see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…For example, Fox and Ralston (2016) identified that social media act as important learning platforms for the evolution of LGBTQþ identity by allowing individuals to seek LGBTQþ-related information and observe the experience and behaviors of role models or other LGBTQþ people. At the same time, social media are leveraged by encouraging LGBTQþ individuals to generate various content such as texts, pictures, and videos to share their opinions, attitudes, and experiences to tell others who they are, what they like and have done (Floegel, 2020;Huttunen et al, 2019;Marwick and Boyd, 2011). Taken together, LGBTQþ people will engage frequently in seeking, posting, sharing, and interacting on social media across diverse contexts to satisfy the need for knowing the self and the need for expressing the self (Floegel and Costello, 2019;Kitzie et al, 2022); thus they will be likely to perceive the context collapse due to the increased awareness or experience of the convergence of information, norms, and generalized others that are originally separated (Davis and Jurgenson, 2014;Marwick and Ellison, 2012).…”
Section: Needs For Self-identity Ofmentioning
confidence: 99%
“…For example, Fox and Ralston (2016) identified that social media act as important learning platforms for the evolution of LGBTQþ identity by allowing individuals to seek LGBTQþ-related information and observe the experience and behaviors of role models or other LGBTQþ people. At the same time, social media are leveraged by encouraging LGBTQþ individuals to generate various content such as texts, pictures, and videos to share their opinions, attitudes, and experiences to tell others who they are, what they like and have done (Floegel, 2020;Huttunen et al, 2019;Marwick and Boyd, 2011). Taken together, LGBTQþ people will engage frequently in seeking, posting, sharing, and interacting on social media across diverse contexts to satisfy the need for knowing the self and the need for expressing the self (Floegel and Costello, 2019;Kitzie et al, 2022); thus they will be likely to perceive the context collapse due to the increased awareness or experience of the convergence of information, norms, and generalized others that are originally separated (Davis and Jurgenson, 2014;Marwick and Ellison, 2012).…”
Section: Needs For Self-identity Ofmentioning
confidence: 99%
“…These are primarily orientation activities: Estimating, probing, scaffolding against what is known and using comparisons to judge the level of change that may be necessary. Some information may be more impactful than others at this stage as Huttenen et al, explain "Deeply meaningful information can serve as a trigger for life change, helping people forward during the transitions" (Huttunen & Kortelainen, 2020), particularly information that is somehow resonant with the individual (Ruthven, 2021).…”
Section: Understandingmentioning
confidence: 99%
“…Do the choices we make about our publications (conference vs journal, single‐ vs double‐ blind, prestige) affect who is represented? These are important questions particularly as our field begins to examine issues of geography (Chang, Gomes, & McKay, 2020; Oduntan & Ruthven, 2021; Zhu & Du, 2020), culture (Binsahl, Chang, & Bosua, 2020; Ma, 2019), gender and gendered experiences (Huttunen & Kortelainen, 2021; Levy & Schneier, 2020; Ruthven, Buchanan, & Jardine, 2018) in relation to information access and use. Ensuring diverse voices are represented among those doing science alongside those studied is not only an ethical good, it also results in more innovative and complete research (Haines, Rose, Odom, & Omland, 2020).…”
Section: Introductionmentioning
confidence: 99%